PENGARUH CITRA SEKOLAH DAN STRATEGI PEMASARAN JASA TERHADAP KEPUTUSAN MEMILIH SEKOLAH DI MTS NEGERI 6 JOMBANG - Arofah, Farikhatul; Suwandi (LPPM STAI Muhammadiyah Probolinggo, 2024)
The decision to choose a school in the current era is a crucial step for parents and students. Choosing the right school will help maximize a child's potential and intelligence, because school is not only a place for learning but also for a child's personality development and character. Public awareness of the importance of education makes parents and students compete to choose schools that will provide the expected results in the future. This research was conducted at MTs Negeri 6 Jombang. This study use a quantitative approach. The study's population consisted of 198 parents of students, the sample taken was 132 parents of students using the Slovin formula with an error rate of 5%, using probability sampling using simple random sampling techniques. The goals of this study include, (1) to find out whether there is an influence of school image on the decision to choose a school at MTs Negeri 6 Jombang, (2) to find out whether there is an influence of service marketing strategies on the decision to choose a school at MTs Negeri 6 Jombang, and (3) To find out whether there is a simultaneous influence of school image and service marketing strategy on the decision to choose a school at MTs Negeri 6 Jombang.